Economic and environmental viability assessment of NASA’s turboelectric distribution propulsion - Alrashed, Mosab; Nikolaidis, Theoklis; Pilidis, Pericles; Alrashed, Wael; Jafari, Soheil (Elsevier, 2020)
The concept of turboelectric-distributed propulsion (TeDP) has become integral to engineering because of its ability to generate electricity. However, social science compels careful evaluations of TeDP’s environmental and economic impacts—out of caution, such elements must be taken up before TeDP is put into practice. Responding to this call, this research investigates TeDP’s economic and environmental viability with a case study of the National Aeronautics and Space Administration’s (NASA) proposal for a TeDP aircraft, N3-X, using technical aspects and real data integration. The economic assessment measures NASA’s N3-X economic added value for aviation manufacturing, operations, and investors as well as net present value, internal rate of return, and payback period. Meanwhile, the environmental assessment looks at carbon monoxide and dioxide and oxides of nitrogen. The economic and environmental evaluation results establish the viability of TeDP.
Keywords: Environment assessment; NASA N3-X; Turboelectric distributed propulsion; Economic value-added